MENGUJI PENGARUH FAKTOR-FAKTOR RATIO TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN ANALISIS REGRESI LINEAR BERGANDA - Astarini, Dewa Ayu Oki; Murapi, Ikang; Apriana, Linda (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This research aims to examine the effect of profitability ratios as measured by Return On Assets (ROA), liquidity ratios as measured by Current Ratio (CR), and solvency ratios as measured by Debt to Total Asset Ratio (DAR) on measured financial performance. with Total Assets Turnover (TATO). The population in this research is Hotel Sahid Jaya Tbk. The data used in this research are financial reports from 2017 to 2021. This research uses multiple linear regression analysis methods which are processed using SPSS version 25 application tools. The results of this research show that the profitability ratio has no effect on financial performance because the company has a good financial position. It is not good in terms of net profit, while the liquidity ratio also has no effect on financial performance, and the solvency ratio (DAR) has no effect on financial performance (TATO). The contribution of this research is the use of assets to obtain and increase profits as well as re-evaluating all current assets owned to pay long and short term debts, so that the company can increase maximum profits.